2010
DOI: 10.1002/psc.1267
|View full text |Cite
|
Sign up to set email alerts
|

The conformational properties of dehydrobutyrine and dehydrovaline: theoretical and solid‐state conformational studies

Abstract: Dehydrobutyrine is the most naturally occurring dehydroamino acid. It is also the simplest dehydroamino acid having the geometrical isomers E/Z. To investigate its conformational properties, a theoretical analysis was performed on N-acetyl-alpha,beta-dehydrobutyrine N'-methylamides, Ac-(E)-DeltaAbu-NHMe and Ac-(Z)-DeltaAbu-NHMe, as well as the dehydrovaline derivative Ac-DeltaVal-NHMe. The phi, psi potential energy surfaces and the localised conformers were calculated at the B3LYP/6-311 + + G(d,p) level of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
(73 reference statements)
0
11
0
Order By: Relevance
“…The conformation β2 is predicted by theoretical calculations for analogous dehydroamino acid amides but generally it has relatively high energy. Interestingly, although the DFT calculations predict the low‐energy conformer β2 for the Ac‐( Z )‐ΔAbu‐NHMe molecule62, it is not confirmed by FTIR analysis20, neither is it adopted in the solid state62. Therefore, the low‐energy conformation β2 is the result of the non‐additive junction of both the C α C β double bond and ester group within the amino acid residue.…”
Section: Discussionmentioning
confidence: 95%
“…The conformation β2 is predicted by theoretical calculations for analogous dehydroamino acid amides but generally it has relatively high energy. Interestingly, although the DFT calculations predict the low‐energy conformer β2 for the Ac‐( Z )‐ΔAbu‐NHMe molecule62, it is not confirmed by FTIR analysis20, neither is it adopted in the solid state62. Therefore, the low‐energy conformation β2 is the result of the non‐additive junction of both the C α C β double bond and ester group within the amino acid residue.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown that modifications of peptide main chain or side chain as N -methylation (Siodłak et al 2006 , 2008 , 2012 ; Broda et al 2005 , 2009 ), C -terminal ester bond (Siodłak et al 2010 , 2011 ; Siodłak and Janicki 2010 ), dehydration of side chain (Buczek et al 2014 ), cyclization (Staś et al 2016a ), and many more (Jwad et al 2020 ; Gil et al 2009 ; Paranthaman 2018 ) have a considerable influence on preferred conformation. This includes the introduction of a five-membered heterocycle, such as oxazole (Siodłak et al 2014a ; Staś et al 2016a , b ) or thiazole, into a peptide main chain as an isosteric replacement of amide group.…”
Section: Introductionmentioning
confidence: 99%
“…αβ‐Didehydro‐α‐amino acids, commonly known as dehydroamino acids (ΔXaa), belong to nonstandard amino acids occurring primarily in natural peptides produced by bacteria and fungi . Dehydroamino acids continuously attract attention in various areas, mainly in synthesis, as designed products or suitable substrates, including asymmetric hydrogenation as well as in the conformational studies . Dehydrophenylalanine (ΔPhe), although scarcely presented in natural compounds, is the most often studied dehydroamino acid .…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to its relatively high stability as well as promising works on dehydrophenylalanyl analogs of naturally occurred peptides . The possible geometrical isomerism Z/E of dehydroamino acids also attracts interest . There are examples of significant differences in biological activities of peptides, which differ only in topography of the dehydroamino acid side chain .…”
Section: Introductionmentioning
confidence: 99%